Evaluasi Budaya Organisasi Dalam Mendukung Perilaku dan Kinerja Pegawai (Studi PT. Nusa Toyotetsu Corp) - Diana Junaedi (Universitas Pendidikan Nasional, 2021)
Employee performance is very important in order to achieve the goals of a company, and to achieve the goals of the company it is necessary to have a good quality of employee performance. In order to be able to create or build the quality of a performance, the company must motivate each employee so that they can produce good quality performance. The purpose of this study is to determine and analyze how the evaluation of organizational culture in supporting employee behavior at PT. Nusa Toyotetsu Corp. This evaluation covers the culture of applying motivation and direction regarding the work discipline carried out by the company. the research was conducted to all employees of PT. Nusa Toyotetsu Corp. which amounted to 1200 people, and the sample of this study were 92 employees who were the total sample from each department. The data analysis technique is obtained from the results of data calculations using multiple linear titrations. and will obtain results that determine that a culture of motivation and application of work discipline greatly affects employee performance.